Libman-Sacks endocarditis in a child with systemic lupus erythematosus: a case report and literature review - Lu, Jingyi; Bao, Shengfang; Xu, Xuemei; Jin, Yingying; Liu, Chenxi; Zhang, Yuqi; Wang, Qian; Jin, Yanliang (Frontiers in Pediatrics, 2024)
Libman-Sacks endocarditis (LSE) is a cardiac condition characterized by the growth of verrucous vegetation. Although relatively rare in children, LSE is nevertheless a known cardiac manifestation of autoimmune diseases, including systemic lupus erythematosus (SLE). The mitral valve is the most commonly affected region, followed by the aortic valve, while the tricuspid and pulmonary valves are rarely affected. The management of established Libman-Sacks vegetation poses significant challenges, often necessitating surgical interventions, although surgery is not the primary treatment modality. Herein, we present the case of a 14-year-old Chinese female patient whose initial lupus manifestation included LSE, among other symptoms and signs that provided insights into the final diagnosis of SLE. After early comprehensive pharmacological treatment, tricuspid regurgitation and vegetation disappeared within 28 days without necessitating cardiac surgery, indicating that the resolution of LSE vegetation in this patient was achieved through a combination of immunosuppressive and anticoagulant therapy. These findings suggest the potential of this treatment approach as a viable model for the management of LSE in young patients.